2019
DOI: 10.1002/aur.2098
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Social Dominance and Altered Neuronal Excitability in the Prefrontal Cortex of Male KCC2b Mutant Mice

Abstract: The K-Cl cotransporter KCC2 is essential in the development of the "GABA switch" that produces a change in neuronal responses to GABA signaling from excitatory to inhibitory early in brain development, and alterations in this progression have previously been hypothesized to play a causal role in autism spectrum disorder (ASD). We investigated the KCC2b (Slc12a5) heterozygous knockout mouse using a battery of rodent behavioral tests relevant to core and comorbid ASD symptoms. Compared to wild-type littermates, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 59 publications
1
6
0
1
Order By: Relevance
“…The study of social dominance in ASD patients is still limited, and a few studies have suggested an atypical way of recognition in these patients when they were asked to judge who is dominant between two persons presented as schematic diagrams or animations [31,32]. Further, a series of studies reported dominant social phenotypes in multiple rodent models associated with ASD [33][34][35]. Thus, current observations support and extend autistic traits of TS2-neo mice using the IntelliCage apparatus.…”
Section: Discussionsupporting
confidence: 53%
“…The study of social dominance in ASD patients is still limited, and a few studies have suggested an atypical way of recognition in these patients when they were asked to judge who is dominant between two persons presented as schematic diagrams or animations [31,32]. Further, a series of studies reported dominant social phenotypes in multiple rodent models associated with ASD [33][34][35]. Thus, current observations support and extend autistic traits of TS2-neo mice using the IntelliCage apparatus.…”
Section: Discussionsupporting
confidence: 53%
“…Rebound excitation, due to the accumulation of Cl − ions following the end of NpHR activation, for example, has been found (Gradinaru et al, 2007 ; Raimondo et al, 2012 ). This caveat may be further compounded in disorders associated with Cl − imbalance such as chronic pain (Coull et al, 2003 ), drug dependence (Ferrini et al, 2013 ; Ostroumov et al, 2016 ), and certain symptoms of autism (Anacker et al, 2019 ). In this context, the recent advent of Cl − permeable opsins may be more promising (Govorunova et al, 2015 ; Wietek et al, 2015 ).…”
Section: Improved Optogenetic Tools Of Potential Utility For Therapeumentioning
confidence: 99%
“…将神 dmPFC) [28] , 其他团队鉴定出下丘脑腹侧前乳核(hypothalamic ventral premammillary nucleus, PMv) [36] 、 腹侧被盖区(ventral tegmental area, VTA) [37] 、NAc [34] 等 与调控社会等级密切相关的脑区. 最近, 中国科学院上 海营养与健康研究所的李海鹏团队 [38] [44] 、钾-氯协同转运蛋白KCC2 [45] 、 Npy1r受体 [46] [53] . 这一发现被认为是精神疾病领域半个世纪内最 重要的发现 [53,54] .…”
Section: 辟了道路 因此在社交unclassified